3D numerical study of heat and mass transfer of moving porous moist objects - Coban, Seda Ozcan; Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2021)
Heat and moisture transfer of two moving moist objects in a channel with convection of hot dry air is investigated numerically. A moving mesh approach is used for providing movement by means of the Arbitrary LagrangianEulerian (ALE) framework. Governing equations for flow field and porous objects are solved by finite element discretization method for the 3D transient problem. Effects of drying air velocity and temperature are simulated by means of temperature, moisture content and heat transfer distributions. Results showed the importance of varying parameters on drying behavior. It was observed that the air velocity also has an increasing effect on evaporation and most reduction in moisture content is obtained at 0.8 m/s air velocity with 63.12% loss. Besides, there are insignificant differences between heat transfer values for fixed and moving objects, differences in average heat transfer values calculated between 6 and 13% for static bed and moving bed.
Keywords: Lattice Boltzmann Method; Immersed Boundary; Forced-Convection; Fluid-Flow; Food Processes; Simulation; Model; Transport; Rehydration; Temperature